LEGAL PRINCIPLES FROM THE SERBIAN CIVIL CODE OF 1844 TO THE DRAFT OF THE CIVIL CODE OF 1934 - Kostovski, Milica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
One hundred and eighty years since the adoption of the Serbian Civil Code for the Principality of Serbia (1844) and ninety years since the publication of the Draft of the Civil Code for the Kingdom of Yugoslavia (1934) are good reasons to compare two acts that represent important points on the development line of Serbian civil law. Considering the volume and complexity of the matter contained in these acts, the paper will pay special attention only to the introductory rules in which fundamental legal principles are proclaimed, such as the prohibition of retroactive application of rights or the prohibition of abuse of rights. Differences in the choice of key principles, in the structure of the introductory part and in the formulation of legal principles clearly testify to the state, political and economic differences between Serbia in 1844 and Yugoslavia in 1934. Certain legal principles that will be analyzed in the paper were inspired by the spirit of the time in which they were created, while others are the result of different foreign influences over a period of ninety years. The comparison of these two acts, in addition to providing us with a factual insight into the state of law in the analyzed periods, also aims to show a certain degree of evolution of law that can be seen in the transition from SCC to the Draft. Using the historical-legal and comparative method, with a brief but necessary overview of the socio-political circumstances, the author will try to present the basic features of the development of civil law.